Reler as Ditaduras no Brasil e Portugal: o realismo mágico em Sombras de reis barbudos, de José J. Veiga, e O dia dos prodígios, de Lídia Jorge - Paulo, Renan Henrique Messias de (Universidade Federal de São Carlos, 2023)
Magical realism has been used as the foundation of literary production, driven by lyricism and the articulation of allegories. Its use contributed to the writing of authors who seek to reflect on and point out the problems of the historical, social and political contexts to which they were subjected. José J. Veiga, with Sobras de reis barbudos, and Lídia Jorge, with O dia dos prodígios, use such resources to criticize and denounce the oppressive regimes under which both countries, Portugal and Brazil, found themselves. In light of the Salazarist Dictatorship (Portugal) and the Military Dictatorship (Brazil), writers developed their narratives with the aim of rescuing national origins and highlighting the abnormality that was plaguing the time. Since the works present comparative possibilities, whether in the narrative architecture or in the themes raised, the research aims, above all, to understand the concerns, estrangement and the presence of echoes of dictatorships reflected in the two novels. Although O dia dos prodígios, a Portuguese novel, was published in 1979, five years after the fall of the dictatorial regime, and Sombras de reis barbudos, released in 1972, came to light in the midst of Brazilian authoritarian rule, in both novels, they are lived, remembered and fabled situations, reports and experiences of these political regimes, which reproduce memories of dark and tyrannical times, so well explored by the two authors.
Rereading the Dictatorships in Brazil and Portugal: magical realism in Sombras de reis barbudos, by José J. Veiga, and O dia dos prodígios, by Lídia Jorge
Keywords: Realismo mágico; Ditadura Salazarista; Ditadura Militar; J.J. Veiga; Lídia Jorge; Magical realism; Salazarist dictatorship; Military Dictatorship; LINGUISTICA, LETRAS E ARTES::LETRAS::LITERATURA BRASILEIRA; LINGUISTICA, LETRAS E ARTES::LETRAS::LITERATURA COMPARADA; LINGUISTICA, LETRAS E ARTES::LETRAS::OUTRAS LITERATURAS VERNACULAS